LINGUISTIC REPRESENTATION OF OSYP MAKOVEY IN THE EPISTOLARY DISCOURSE OF OLHA KOBYLIANSKA - Антофійчук, Алла (SWorldJournal, 2026)
The article presents a comprehensive linguistic analysis of the representation of Osyp Makovey’s figure in the epistolary discourse of Olha Kobylianska. The relevance of the study is determined by the need to comprehend the role of figures who ensured li